Comparative efficacy and safety of anti-vascular endothelial growth factor regimens for neovascular age-related macular degeneration: systematic review and Bayesian network meta-analysis - Lu Ye; Zhao Jiaqi; Wang Jianchao; Feng Zhaohui; Yao Liang; Zhang Xiaohui (SAGE Publishing, 2020)
Background: As a debilitating neurodegenerative disease, neovascular age-related macular degeneration (nAMD) accounts for more than 90% of severe visual loss or legal blindness among AMD patients. Anti-vascular endothelial growth factor (VEGF) had been applied widely in nAMD treatment. To date, debate regarding efficacy and safety still exists among different anti-VEGF regimens as management of nAMD. To provide substantial evidence for clinical nAMD treatment, this study ranks the priority of anti-VEGF regimens via Bayesian network meta-analysis (NMA), comparing data collected from randomized controlled trials (RCTs). Methods: We searched PubMed Central, MEDLINE Ovid, Embase Ovid, ISRCTN, ICTRP and ClinicalTrials. gov from a database established until 1 April 2019 systematically for anti-VEGF regimens. Bayesian NMA with random-effect was conducted to compare efficacy and safety and rank priority of anti-VEGF regimens. The primary efficacy and safety outcomes were the proportion of patients gaining 15 or more letters, and the incidence of arterial thromboembolic (ATC) events. The effect measure is the standard mean difference (SMD), or the odds ratio (OR) with their 95% confidence interval (CI). The study protocol is registered with PROSPERO, number CRD42019132243. Results: We obtained 6467 citations and identified 29 RCTs including 13,596 participants; 86% of these trials were low risk or of uncertain risk bias. In NMA, ORs compared with sham injection for the proportion of patients gaining 15 or more letters (12,699 participants from 23 trials) ranged from 4.05 [95% Bayesian credible interval (CrI) 1.62-10.11] for ranibizumab quarterly regimen to 8.57 (95% CrI 4.66-15.73) for a ranibizumab treat-and-extend regimen. No difference was found between sham injection and anti-VEGF regimens for ATC events (11,500 participants from 18 trials). Results for the primary outcome did not substantially change in sensitivity analyses after removing studies at high risk of bias and small sample size ( n  < 100), respectively. Conclusion: The treat-and-extend regimen of ranibizumab and aflibercept are the preferred anti-VEGF regimens for nAMD. Bevacizumab treat-and-extend regimens need more head-to-head comparisons with other regimens or sham injection for advanced application. The treat-and-extend regimen proved to be the most effective regimen for each anti-VEGF drug in the NMA. Pegaptanib every 6 weeks and Conbercept quarterly are unable to satisfy the best corrected visual acuity (BCVA) improvement requirement of nAMD patients.